Incidence of new-onset left bundle branch block and predictors of new permanent pacemaker following transcatheter aortic valve replacement with the Portico™ valve. (9th March 2018) - Walther, Thomas; Manoharan, Ganesh; Linke, Axel; Möllmann, Helge; Holzhey, David; Worthley, Stephen G; Kim, Won-Keun; Schäfer, Ulrich
Abstract: OBJECTIVES: To examine the incidence and timing of new-onset left bundle branch block (LBBB) and new permanent pacemaker implantation (PPI) in patients undergoing transcatheter aortic valve implantation (TAVI) using the repositionable, self-expanding Portico™ TAVI system (St. Jude Medical, St Paul, MN, USA). Clinical impact and periprocedural factors associated with new PPI were also assessed. METHODS: A total of 198 high-risk patients without pre-existing pacemaker [83.1 ± 4.7 years, 77.3% women, mean Society of Thoracic Surgeons (STS) 5.8%] from the Pre-CE Mark Portico TAVI system study were prospectively analysed. Twelve-lead electrocardiographic and echocardiographic data were collected prior to, during and after the procedure. Clinical follow-up was performed at 1 year. RESULTS: Transfemoral implantation of the Portico valve was associated with a new PPI rate of 15.2% at 30 days and 16.7% at 1 year. Overall, 53 of the 187 patients without pre-existing LBBB developed new-onset LBBB at 1 year (28.3%); 23 occurred during the procedure. At 30 days, new-onset LBBB spontaneously resolved in 61.0% of patients. New-onset LBBB post-TAVI was not associated with new PPI ( P = 0.64); 8 of the 53 patients required new PPI. Multivariable regression analyses revealed pre-existing right bundle branch block ( P = 0.004) and aortic annulus diameter ( P = 0.001) as independent predictors of new PPI. New PPI at discharge ( n = 29) was not associated with increased freedom from all-cause (odds ratio 92.7%, 95% confidence interval 73.7–98.1%; P = 0.49) and cardiovascular (odds ratio 96.6%, 95% confidence interval 77.9–99.5%; P = 0.47) mortality at 1 year. CONCLUSIONS: The Portico TAVI system demonstrated an acceptable rate of new PPI at 1 year without increased mortality risk to patients. New-onset LBBB was common during the procedure, with the majority of events spontaneously resolving by 30 days. No intraprocedural factors were shown to independently predict new PPI. Clinical trial registration number: NCT01493284.